Cytotoxic Isobractatin (Prenylated Xanthone) Epimer Mixture of Garcinia eugenifolia - Sri Hartati; I Ketut Triyono; Sri Handayani (Universitas Gadjah Mada, 2014)
In search of bioactive anti-cancer compounds from natural products has been found isobractatin from n-hexane extract of Garcinia eugenifolia. Isolation was done through the stages of maceration and column chromatography. Elucidation of the structure was analyzed by spectroscopy of UV-Vis, FTIR, LC-MS, NMR proton and carbon one and two dimension data. The results found three compounds isolated from G. eugenifolia. The three compounds were stigmasterol, prenylated xanthone isobractatin and its epimer (in a mixture). The mixture of isobractatin and its epimer showed cytotoxic activity against breast cancer cell line T47D with IC50 = 17 µg/mL.